AUDIT KURIKULUM OPERASIONAL SEKOLAH (KOS) DAN IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - M. Fadli mubarak; Suardi; Idawati (STKIP Subang, 2026)
This research was conducted due to the challenges in managing the School Operational Curriculum (KOS) within the Independent Curriculum framework, which sometimes only reaches the administrative level without in-depth reflection at the elementary school level. The purpose of this study was to evaluate the KOS document, analyze the implementation of differentiation and integration of the Pancasila Student Profile, and examine the curriculum evaluation mechanism at SDN 92 Burrung. The method used was descriptive qualitative research with data collection techniques through interviews, observations, document studies, and questionnaires with the principal and teachers. The results showed that the KOS document was up-to-date, but the implementation of differentiated learning still needed strengthening in terms of products and processes, while the integration of P5 was running according to plan. These findings demonstrate the importance of regular internal audits to maintain the quality of curriculum management. The novelty of this study is the contextual curriculum audit approach in rural elementary schools that combines direct observation with teacher reflection. This study provides recommendations for curriculum improvement based on field data for elementary education practitioners.